Evolution of interfacial defects and energy losses during aging of organic photovoltaics - Liu P.; Huang Y.; Wang Z.; Liu W.; Yap B.; He Z.; Wu H. (Elsevier B.V., 2025)
As the power conversion efficiencies of Organic Solar Cells (OSCs) approach 20 %, the stability of the device becomes an increasingly urgent issue. To enhance device stability, it is crucial to identify potential loss mechanisms. In this study, we investigated the trap-state-dependent degradation mechanism of OSCs by directly comparing devices with different hole transport layers (HTLs) that introduce distinct interfacial defect distributions. Employing electrochemical impedance spectroscopy (EIS), Fourier transform photocurrent spectroscopy (FTPS), electroluminescence quantum efficiency (EQEEL), and temperature-dependent J-V techniques, we unraveled the relationship between device degradation and interfacial trap states and energy loss in PM6:Y6 devices. A lower density of interfacial deep traps is evidently correlated with smaller non-radiative recombination losses during the aging of devices based on PEDOT:PSS. Conversely, a higher density of deep traps in aged devices with WS2 interlayers and HTL-free configurations is presumed to be responsible for a significant increase in non-radiative recombination losses. The escalating deep-trap-state density in aged devices is observed to elevate carrier recombination, consequently deteriorating device performance. Beyond the scope of the energy balance theory, an additional factor, probably attributed to the change in the work function of ITO, was found to contribute significantly to energy loss in aged cells, particularly in HTL-free devices. These results highlight the potential for improving device stability via interface engineering. ? 2024 Elsevier B.V.